Pharmacological interventions for prevention and management of delirium in intensive care patients: a systematic overview of reviews and meta-analyses. Issue 2 (6th February 2019) - Barbateskovic, Marija; Krauss, Sara Russo; Collet, Marie Oxenboell; Larsen, Laura Krone; Jakobsen, Janus Christian; Perner, Anders; Wetterslev, Jørn
Abstract : Objectives: We assessed the evidence from reviews and meta-analyses of randomised clinical trials on the effects of pharmacological prevention and management of delirium in intensive care unit (ICU) patients. Methods: We searched for reviews in July 2017 in: Cochrane Library, MEDLINE, Embase, Science Citation Index, BIOSIS Previews, CINAHL and LILACS. We assessed whether reviews were systematic according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and assessed the methodological quality using ROBIS. Outcome measures: Primary outcomes: all-cause mortality, serious adverse events, prevention of delirium and management of delirium. Secondary outcomes: quality of life; non-serious adverse events and cognitive function. Results: We included 378 reviews: 369 narrative reviews, eight semisystematic reviews which failed on a maximum of two arbitrary PRISMA criteria and one systematic review fulfilling all 27 PRISMA criteria. For the prevention of delirium, we identified the one systematic review and eight semisystematic reviews all assessing the effects of alpha-2-agonists. None found evidence of a reduction of mortality (systematic review RR 0.99, 95% CI 0.79 to 1.24). The systematic review and three semisystematic reviews found no evidence of an effect for the prevention of delirium (systematic review RR 0.85, 0.63 to 1.14). Conversely, four semisystematic reviews found a beneficial effect. Serious adverse events, quality of life, non-serious adverse events and cognitive function were not assessed. We did not identify any systematic or semisystematic reviews addressing other pharmacological interventions for the prevention of delirium. For the management of manifest delirium, we did not identify any systematic or semisystematic review assessing any pharmacological agents. Conclusion: Based on systematic reviews, the evidence for the use of pharmacological interventions for prevention or management of delirium is poor or sparse. A systematic review with low risk of bias assessing the effects of pharmacological prevention of delirium and management of manifest delirium in ICU patients is urgently needed. PROSPERO registration number: CRD42016046628.